2021
DOI: 10.1002/prp2.742
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: Can International Consortium of Health Outcomes Measurement standard sets align outcomes accepted for regulatory and health technology assessment decision‐making of oncology medicines

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Non-oncology conditions were selected given previous work has examined uptake across oncology HTAs. 12,13 and where no appropriate NICE HTAs were identified, alternative COS were selected, using the same criteria of publication between 2015 and 2019 with patient involvement. The most recently published reports which matched a COS were included, with outcomes compared to core outcomes from the corresponding COS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-oncology conditions were selected given previous work has examined uptake across oncology HTAs. 12,13 and where no appropriate NICE HTAs were identified, alternative COS were selected, using the same criteria of publication between 2015 and 2019 with patient involvement. The most recently published reports which matched a COS were included, with outcomes compared to core outcomes from the corresponding COS.…”
Section: Methodsmentioning
confidence: 99%
“…However, it should be noted that these outcome sets are developed for routine care, unlike COS which are produced specifically for research so are more relevant for HTAs. 12 Additionally, a review of technology appraisal oncology scopes found that in the majority of cases there was complete overlap with those outcomes in COS; in a small number of exceptions the COS included two additional outcomes to those specified in the scope. 13 Other work has investigated a trial funder and member of INAHTA, the National Institute for Health Research Health Technology Assessment (NIHR HTA), examining their recommendation for applicants to search for a COS to include in their trial.…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes included in these HTAs were compared to core outcomes included in the matching COS. Non-oncology conditions were selected given previous work has examined uptake across oncology HTAs. 12,13 The results are presented through tables, graphs and using descriptive statistics. The analysis was performed using Excel 2019.…”
Section: Methodsmentioning
confidence: 99%
“…and therefore will be captured as part or routine care by the provider. We are hopeful that ongoing international efforts at standardizing outcomes measurements 43 may help improve technical efficiencies. Where legally possible, regulators could help catalyze broad agreement on a given end point (see below).…”
Section: Alignment Of Stakeholder Interestsmentioning
confidence: 99%